Promising Breeding Material from Triticum Turgidum L. - Romanov, Boris; Pimonov , Konstantin; Sorokina, Irina (KnE Life Sciences, 2021)
Turgid wheat is distinguished by a large multi-grain ear. Therefore, the involvement of its varieties in the selection process to increase the productivity of winter durum wheat is very promising. This paper shows the results of creating a highly productive source material to improve the production capabilities of existing varieties of winter hard and turgid wheat. To do this, a cross was performed between a loose-leaved multi-grain variety var.martensii with a large-seeded and dense-leaved var.salomonis. By weight of the grain from the ear, the resulting hybrids significantly exceeded the original parent forms and the zoned varieties of winter hard and turgid wheat, cultivated simultaneously with them, but they were taller. When a hybrid was crossed with a modern low-growing variety of Terra, more productive forms were produced relative to the zoned varieties and the same short-stem forms, which can be used as a promising source of breeding material. The selected hybrids, both individually and on average, clearly outperformed the zoned varieties of durum and turgid wheat in terms of grain weight per ear. The production characteristics of the ear on average for the hybrid were as follows: the length of the ear was 7.6 cm, and 18.9 spikelets and 57.5 grains were formed. Keywords: Triticum turgidum, varieties, hybrid forms, productivity, source material, zoned varieties